Effect of polystyrene nanoplastics on the activated sludge process performance and biomass characteristics. A laboratory study with a sequencing batch reactor. (1st March 2023) - Alvim, C. Bretas; Ferrer-Polonio, E.; Bes-Piá, M.A.; Mendoza-Roca, J.A.; Fernández-Navarro, J.; Alonso-Molina, J.L.; Amorós-Muñoz, I.
Abstract: The fate and presence of nanoplastics in wastewater treatment systems is a topic of increasing interest. Furthermore, challenges related to their quantification and identification have made it difficult to set up experimental conditions and compare results between studies. In this study, the effect of 100 nm polystyrene nanoplastics on activated sludge was evaluated. A concentration of 2 μg/L was used to continuously feed a sequencing batch reactor (SBR-NPs). Under the experimental conditions used in this study, no changes were observed in the process performance of the SBR-NPs compared to the reactor used as a control. Neither nitrification nor organic matter removal efficiency, which was 96% for both SBRs, were affected by the presence of 100 nm polystyrene nanoplastics, which suggests that the tested nanoplastics were not sufficiently toxic to the biomass. Although no significant differences in the relative abundances of predominant phyla between SBR-Control and SBR-NPs were observed, a slight shift in the relative abundance of Patescibacteria (1.5 ± 0.6% and 3.7 ± 0.8% in SBR-Control and SBR-NPs, respectively, at the end of the test) occurred . The higher abundance of this phylum in SBR-NPs compared to SBR-Control may suggest that these bacteria have some sensitivity to the presence of 100 nm polystyrene nanoplastics. Furthermore, even with the absence of nitrification inhibition, it was observed stagnation of the growth of Nitrotoga bacteria in SBR-NPs, which also suggests that the polystyrene nanoplastics could have an inhibitory effect on these cells and an impact on nitrification in the long term. Highlights: Organic matter removal was not affected by 100 nm polystyrene nanoplastics. Differences between the microbial populations in SBRs (control and with NPs) were found. Nitrotoga bacteria abundance was reduced in SBR with 100 nm polystyrene nanoplastics. Nanoplastics enhanced the abundance of Patescibacteria in the activated sludge. Moderate heteroaggregation of nanoplastics was found in the activated sludge.